The Analysis Of Business, Risk, And Development Strategy Of Minapadi (Paddy-Fish Integration Farming System) In Sleman District - Muhammad Nur Prasetyo; Slamet Hartono; Masyhuri Masyhuri (Agro Ekonomi, 2018)
This study aims (1) to determine the income and feasibility of cultivation business using minapadi system (2) to know the level of cost risk, income and profit of farming minapadi, (3) to know the development strategy of cultivation using minapadi system in Sleman District of Yogyakarta. To analyse and interpret the data, it used descriptive analysis method. The location of the research was determined purposively it was in Seyegan Sub District. The number of respondents in this research was 43 farmers which consist of 23 minapadi farmers and 20 non minapadi farmers. The analysis used in this research was income, feasibility, risk and SWOT analysis. The result of the analysis showed that the income and profit of minapadi farmers are more than the non-minapadi farmers. The feasibility analysis of farming system in conducting the cultivation using minapadi system and non minapadi system respectively at 1.43 and 1.27, so that these two businesses are worthy to run since the value of R/C ratio was more than 1. The risk analysis shows that in the farm integrating minapadi has lower risk of costs, revenues, and profits. The appropriate strategy for the development of minapadi farming is the S-T strategy which is by utilizing the strengths to minimize the threats.